Invincible. Volume 12 - Kirkman, Robert (Image Comics, Inc. : Skybound, 2025)
"In the aftermath of his battle with Conquest, Invincible and his world are left in ruins. Can he really be the hero that the people Earth need to protect them? Meanwhile, deep in space, Omni-Man and Allen the Alien prepare for the impending Viltrumite War!